2019
DOI: 10.1002/oa.2848
|View full text |Cite
|
Sign up to set email alerts
|

Aging methods and age‐at‐death distributions: Does transition analysis call for a re‐examination of bioarchaeological data?

Abstract: Age estimation of adult skeletal remains is notoriously difficult because the degenerative change of adult skeletons is far more variable across individuals, populations, and anatomical regions than the developmental changes that occur during growth. Additionally, age mimicry makes it difficult to discern between the true population age structure and the age structure produced as an artifact of the reference sample. Transition analysis is an age estimation method that was developed to improve the accuracy of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 73 publications
(126 reference statements)
4
22
0
Order By: Relevance
“…This is supported by the improved ability of TA to estimate the age of older adults (Lopez‐Cerquera & Casallas, 2019). However, such a conclusion is suspect because in a study comparing survivorship in skeletons from multiple sites in post‐medieval Ireland, Clark et al (2020) found that survivorship was lowest among individuals from Coombe/Cork St. and North King St. It is perhaps more likely that the greater survivorship of the individuals from St. Luke and St. Michan, as estimated from the skeletons from Coombe/Cork St. and North King St., could be a result of user error or a tendency in the method itself to overestimate age‐at‐death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is supported by the improved ability of TA to estimate the age of older adults (Lopez‐Cerquera & Casallas, 2019). However, such a conclusion is suspect because in a study comparing survivorship in skeletons from multiple sites in post‐medieval Ireland, Clark et al (2020) found that survivorship was lowest among individuals from Coombe/Cork St. and North King St. It is perhaps more likely that the greater survivorship of the individuals from St. Luke and St. Michan, as estimated from the skeletons from Coombe/Cork St. and North King St., could be a result of user error or a tendency in the method itself to overestimate age‐at‐death.…”
Section: Discussionmentioning
confidence: 99%
“…Bioarchaeologists should continue to exercise caution when drawing conclusions about survivorship in past populations. Second, bioarchaeologists should avoid making direct comparisons between survivorship estimated using different age methods (Clark et al, 2020), including survivorship distributions calculated from known‐age‐at‐death samples, unless the differences are acknowledged and discussed at length. Additionally, bioarchaeologists should identify socioeconomic factors that could contribute to differences in survivorship even in a single population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bayesian transition analysis is a suitable method for modeling a sequential variable in which the order of the steps is determined by a skeletal trait and its morphological changes are constantly changing (17). This analysis is based on a cumulative probability model in which age can be considered as an independent variable and estimated for a person transitioning from one age to another (18)(19)(20)(21). By estimating the regression slope for age and tracking each transition of the regression model, a cumulative probability was obtained for each subgroup.…”
Section: Bayesian Transition Analysismentioning
confidence: 99%
“…Taking the estimates as the best approximations to true chronological age, studies are using them as data to investigate secondary factors, such as the effects of indirect indicators of social disparities, differential access to resources, and pathophysiological stress (e.g., body size, sex, socioeconomic stature, linear enamel hypoplasia), which create mortality disparities between groups (DeWitte, 2009, 2010, 2014; DeWitte & Hughes‐Morey, 2012; Fojas, 2016; Wilson, 2014; Yaussy et al, 2016). Moreover, some studies have even called for the re‐evaluation of previously studied archeological skeletal samples with TA2, expecting more meaningful estimates and greater insights (Clark et al, 2020).…”
Section: Introductionmentioning
confidence: 99%